2007
DOI: 10.1002/lt.20932
|View full text |Cite
|
Sign up to set email alerts
|

De novo nonalcoholic fatty liver disease after liver transplantation

Abstract: Hepatic steatosis is a recognized problem in patients after orthotopic liver transplant (OLT). However, de novo development of nonalcoholic fatty liver disease (NAFLD) has not been well described. The aim of this study was to determine the prevalence and predictors of de novo NAFLD after OLT. A retrospective analysis was performed on 68 OLT patients with donor liver biopsies and posttransplantation liver biopsies. Individual medical charts were reviewed for demographics, indication for OLT, serial histology re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
144
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(149 citation statements)
references
References 29 publications
2
144
1
2
Order By: Relevance
“…This is higher than the previously reported prevalence of 18%-40% in LT recipients. (11)(12)(13) Although the most frequent indication for LT in our study group was alcoholic cirrhosis (26.3%), which poses an increased risk of posttransplant steatosis, another study with an even higher proportion of patients with alcoholic cirrhosis reported a lower prevalence of posttransplant steatosis. (11) The high prevalence of posttransplant overweight/obesity (52.4%), hypertriglyceridemia (55.7%), and DM (29.4%) among our patients may explain the high prevalence of steatosis.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This is higher than the previously reported prevalence of 18%-40% in LT recipients. (11)(12)(13) Although the most frequent indication for LT in our study group was alcoholic cirrhosis (26.3%), which poses an increased risk of posttransplant steatosis, another study with an even higher proportion of patients with alcoholic cirrhosis reported a lower prevalence of posttransplant steatosis. (11) The high prevalence of posttransplant overweight/obesity (52.4%), hypertriglyceridemia (55.7%), and DM (29.4%) among our patients may explain the high prevalence of steatosis.…”
Section: Discussionmentioning
confidence: 59%
“…(10) Posttransplant NAFLD affects 18%-40% of liver transplantation (LT) recipients (11)(12)(13) and even 39%-70% (14,15) of those transplanted for NAFLD-related cirrhosis. Risk factors of posttransplant NAFLD include pretransplant and posttransplant obesity, (11)(12)(13) alcoholic cirrhosis as an indication for LT, posttransplant DM, hyperlipidemia, hypertension, tacrolimus (FK-506) administration, and pretransplant graft steatosis. (11) In a study by Finkenstedt et al, (16) the PNPLA3 genotype of the recipient (but not the donor) was associated with the development of posttransplant steatosis.…”
mentioning
confidence: 99%
“…In recent studies, the development of de novo steatosis does not only depend on the risk factors reported for recurrent NAFLD/NASH but also on patient obesity at the time of liver biopsy, tacrolimus-based immunosuppression, alcoholic liver disease as the primary indication for LT, and pretransplant liver graft steatosis. (5,6) There are very few studies addressing the histological evolution and longterm natural history of NAFLD after LT, regardless of recurrent or de novo steatosis. In particular, the clinical impact of graft steatosis on the longterm outcome of LT recipients remains unclear.…”
Section: See Article On Page 644mentioning
confidence: 99%
“…Obesity can also affect the graft in the late postoperative period. In patients with general indications for liver transplantation, the incidence of steatosis ranges from 18% 43 to 40% 44 and the incidence of non-alcoholic steatohepatitis, from 9% 43 to 13% 44 . Excess weight has been considered a risk factor for such types of involvement.…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%